Pengaruh Pendidikan Kesehatan Tentang Pemeriksaan Payudara Sendiri Terhadap Pengetahuan dan Perilaku pada Mahasiswi - Siti Nurjanah; Juniar Nur (STIKES Karya Husada Kediri, 2019)
The incidence rate of breast problems increases because of the lack of knowledge or information that makes people come late to the hospital for examining their breast problems which have reached the moderate stage. In fact, breast problems can be avoided by doing self-breast examination (SADARI). Therefore, this research was purposed to find out the effects of health education about self-breast examination on the knowledge and behavior of the second-semester-female students of S1 Nursing Program - University of Nahdlatul Ulama Surabaya (UNUSA).The design of this research was pre-experimental using one group pretest-posttest design that involved all of the female students of UNUSA, totaling 134 students. 50 samples were chosen using stratified random sampling technique. The independent variable was the health education about self-breast examination, whereas the dependent variable was the knowledge and behavior dealing with the technique of self-breast examination possessed by the female students. Moreover, questionnaires and observation sheet were used as the instruments to collect the data which were analyzed using Wilcoxon Signed-Rank Test.The result of this research showed the difference between the knowledge and behavior dealing with self-breast examination before and after receiving treatment in which ρ = 0.000 showing that ρ < 0.05. It showed that H0 was rejected describing that the health education about self-breast examination brought some effects on the female students’ knowledge and behavior.The frequency of receiving the knowledge or information about self-breast examination will make people, especially female students, easier to apply self-breast examination technique daily. Hence, they are expected to do it once in a month within the first week after menstrual period.